DEVELOPING DIGITAL - BASED COMIC MEDIA IN TEACHING MATHEMATICS FOR ELEMENTARY SCHOOL STUDENTS - Muhamad Afandi; Rida Fironika Kusumadewi; Ridha Dwi Lestari (JMIE (Journal of Madrasah Ibtidaiyah Education), 2021)
This research aims to develop digital-based comic media on addition and subtraction materials of mathematics for elementary school students at grade II. This research was motivated by a lack of knowledge of students on addition and subtraction materials. The novelty of this media is in the form of files without using sheets of paper. This study used ADDIE model (Anlysis, Design, Develop, Implement, and Evaluate). Based on the five stages of development of comic media resulted from the feasibility of 90% while the practicality of teachers obtained a percentage of 90% and practicality of students obtained a percentage of 93%. The use of products gets a percentage of 86% with the category "excellent". This study has an implication that that the use of learning media makes students more actively involved in the learning process especially those in elementary schools. Therefore, teachers are supposed to maintain their creativity in teaching.